Espectroscopia de impedância eletroquímica aplicada ao estudo das reações heterogêneas em ânodos dimensionalmente estáveis - Carvalho, Liliane A. de; Andrade, Adalgisa R. de; Bueno, Paulo Roberto [UNESP] (Sociedade Brasileira de Química, 2006)
This paper discusses different aspects related to the application of electrochemical impedance spectroscopy (EIS) in the study of heterogeneous electrochemical reactions occurring on Dimensionally Stable anodes (DSA®). The most relevant aspects of the semiconductor/electrolyte interface, the application of the EIS classical equivalent circuit approach and the ac porous model in DSA are presented. The paper shows that DSA type electrodes can be consistently investigated by using the ac porous model and an analysis is presented showing the advantage of applying this kind of approach to study heterogeneous reactions on DSA electrodes. Furthermore, some preliminary results on Ti/Ru0,3Ti(0,7-x)Sn x O2 based electrodes are presented to exemplify the use of the ac porous model analysis.
Electrochemical impedance spectroscopy applied in the study of heterogeneous reactions at dimensionally stable anodes
Keywords: dimensionally stable anodes; electrochemical impedance spectroscopy; semiconductors oxide electrode